Association of Serum Lipoprotein (a) With the Requirement for a Peripheral Artery Operation and the Incidence of Major Adverse Cardiovascular Events in People With Peripheral Artery Disease. Issue 6 (17th March 2020) - Golledge, Jonathan; Rowbotham, Sophie; Velu, Ramesh; Quigley, Frank; Jenkins, Jason; Bourke, Michael; Bourke, Bernie; Thanigaimani, Shivshankar; Chan, Dick C.; Watts, Gerald F.
Abstract : Background: The aim of this study was to assess the relationship between serum lipoprotein (a) (Lp[a]) concentration and the requirement for peripheral artery disease (PAD) operations or incidence of major adverse cardiovascular events. Methods and Results: A total of 1472 people with PAD presenting with intermittent claudication (n=355), abdominal aortic aneurysm (n=989) or critical limb ischemia (n=128) were prospectively recruited from 4 outpatient clinics in Australia. Lp(a) was measured in serum samples collected at recruitment using an immunoassay. Participants were followed for a median (interquartile range) of 2.4 (0.1–6.1) years to record requirement for any PAD operation, defined to include any open or endovascular PAD intervention (lower limb peripheral revascularization, abdominal aortic aneurysm repair, other aneurysm repair, or carotid artery revascularization). Myocardial infarctions, strokes, and deaths were also recorded. The association of Lp(a) with events was assessed using Cox proportional hazard analysis adjusting for traditional risk factors. Participants with Lp(a) ≥30 mg/dL had a greater requirement for any PAD operation (hazard ratio, 1.20, 95% CI, 1.02–1.41) and lower limb peripheral revascularization alone (hazard ratio 1.33, 95% CI, 1.06–1.66) but no increased risk of major adverse cardiovascular events or all‐cause mortality. Lp(a) ≥50 mg/dL and a 40 mg/dL increase in Lp(a) were also associated with an increased risk of lower limb peripheral revascularization alone but not with other outcomes. Conclusions: In participants with PAD referred for hospital management those with high Lp(a) had greater requirement for lower limb peripheral revascularization but Lp(a) was not consistently associated with other clinical events.